Asymmetric Total Synthesis and Anti-Inflammatory Activity of Berbamine, Oxyacanthine, and Related Intermediates - Li Xiang (586649) (2025)
The first asymmetric total synthesis of the bisbenzylisoquinoline alkaloids berbamine (1a) and oxyacanthine (1b) has been accomplished by employing Noyori asymmetric hydrogenation for chirality installation and leveraging copper-mediated Ullmann coupling for macrocycle formation. Our synthesis unequivocally confirmed the sample misidentification of 1a, as indicated in our previous work. Evaluation of anti-inflammatory activities revealed that both synthetic and natural berbamine or oxyacanthine comparably suppressed gene expression of pro-inflammatory cytokines IL-6 and IL-1β in LPS-stimulated RAW 264.7 macrophages. Notably, intermediate 15a displayed potent anti-inflammatory activity coupled with minimal cytotoxicity, emerging as a promising lead candidate for the development of novel anti-inflammatory agents.